Dijkstra Algorithm Application: Shortest Distance between Buildings - Deepa, G.; Kumar, Priyank; Manimaran, A.; Rajakumar, K.; Krishnamoorthy, V. (International Journal of Engineering and Technology, 2018)
The shortest path algorithm is one of the best choices for implementation of data structures. The shortest path (SP) problem involves the problem of finding a suitable path between â€œtwo vertices or nodes in a graphâ€ in such a way that the sum of the weights of its component edges is minimal. There are many theories for solving this problem one of the widely used way solution for solving this problem is Dijkstraâ€™s algorithm (DA) which is also widely used in many engineering calculation works also. There are two types of DA one is the basic one and other one is optimized. This paper is focused on the basics one which provides a shortest route between source node and the destination node. Main focus has been kept on keeping the work simple and easy to understand with some basic concepts .Storage space and operational efficiency improvement has been tried to improve.Â